Tingkat Stres Profesional di Kalangan Guru Pendidikan Jasmani di Yordania dan Hubungannya dengan Variabel Tertentu - Lubna Mahmoud Obeidat; Mohammad Omar Al-Momani; Saa Saleh Obeidat (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The study aimed to identify the level of professional stress facing physical education teachers in the Hashemite Kingdom of Jordan and its relationship to the variables of gender and years of experience. Materials and methods. A descriptive analytical approach was followed, in addition to using a questionnaire consisting of (30) items as a study tool. The questionnaire was administered to a sample of (294) male and female physical education teachers during the second semester of the 2024/2025 academic year. Result. After conducting appropriate statistical processing, the study concluded that the level of professional stress among physical education teachers was moderate, with an arithmetic mean of (2.69) and a standard deviation of (0.52). Furthermore, there were no statistically significant differences in their level of professional stress attributable to the variables of gender (male, female) and years of experience (less than 10 years, more than 10 years). Conclusion. The study demonstrated that physical education teachers in Jordan encounter moderate occupational stress, attributable to substandard infrastructure. No significant differences in stress levels were observed that could be attributed to gender or years of experience, suggesting that stress originates from the work environment itself.